Nutritional intakes of highly trained adolescent swimmers before, during, and after a national lockdown in the COVID-19 pandemic - Newbury, J. W.; Foo, W. L.; Cole, M.; Kelly, A. L.; Chessor, R. J.; Sparks, S. A.; Faghy, M. A.; Gough, H. C.; Gough, L. A. (PLOS ONE, 2022)
Strict lockdown measures were introduced in response to the COVID-19 pandemic, which caused mass disruption to adolescent swimmers` daily routines. To measure how lockdown impacted nutritional practices in this cohort, three-day photograph food diaries were analysed at three time points: before (January), during (April), and after (September) the first UK lockdown. Thirteen swimmers (aged 15 ± 1 years) from a high-performance swimming club submitted satisfactory food diaries at all time points. During lockdown, lower amounts of energy (45.3 ± 9.8 vs. 31.1 ± 7.7 kcal·kg BM·day-1, p<0.001), carbohydrate (5.4 ± 1.2 vs. 3.5 ± 1.1 g·kg BM·day-1, p<0.001), protein (2.3 ± 0.4 vs. 1.7 ± 0.4 g·kg BM·day-1, p = 0.002), and fat (1.6 ± 0.4 vs. 1.1 ± 0.3 g·kg BM·day-1, p = 0.011) were reported. After lockdown, no nutritional differences were found in comparison compared to before lockdown (energy: 44.0 ± 12.1 kcal·kg BM·day-1; carbohydrate: 5.4 ± 1.4 g·kg BM·day-1; protein: 2.1 ± 0.6 g·kg BM·day-1; fat: 1.5 ± 0.6 g ·kg BM·day-1, all p>0.05), despite fewer training hours being completed (15.0 ± 1.4 vs. 19.1 ± 2.2 h·week-1, p<0.001). These findings highlight the ability of adolescent swimmers to alter their nutrition based on their changing training circumstances when receiving sport nutrition support. However, some individuals displayed signs of suboptimal nutrition during lockdown that were not corrected once training resumed. This warrants future research to develop interactive education workshops that maintain focus and motivation towards optimal nutrition practices in isolated periods away from training.